Analysis of Total Protein and Non-Protein Nitrogen in Durian Seeds and Durian Flour Using the Kjeldahl Method - Apul Sitohang; Jansen Silalahi; Wiyanti Fransisca Simanullang (Postgraduate, University of Mataram, 2025)
Durian seeds, often regarded as agricultural waste, contain notable amounts of macronutrients, particularly proteins, that warrant further exploration for potential food and feed applications. This study aimed to evaluate the total nitrogen, protein, and non-protein nitrogen (NPN) contents in fresh and processed seeds of three local durian (Durio zibethinus) cultivars Bintana, Pelangi, and Bawor using the Kjeldahl method. Fresh seeds and their corresponding flours were analyzed for moisture content, total nitrogen, and protein fractions, including actual protein and NPN levels. The results revealed significant variations across cultivars and between fresh and processed samples. Bintana exhibited the highest protein content in both fresh and flour forms, followed by Pelangi and Bawor. Processing, including soaking, drying, and flour preparation, was found to increase measurable protein content but may also contribute to protein denaturation. Overall, durian seeds, particularly from the Bintana variety, demonstrate promising nutritional potential as a functional food ingredient or alternative protein source.